Adhd symptomatology in preschoolers: evidence of the validity of an instrument for its identification (ISTDAH36). - Panduro Paredes, José Antonio (2022)
An instrument for early identification of ADHD symptomatology is proposed. Data were obtained from 358 mother-child dyads in Lima and Callao, in which mothers reported on the symptomatology of their preschool children. The analyses supported the conception of symptomatology as a continuum; they corroborated the two-dimensionality of the disorder’s symptomatology (Inattention and Hyperactivity/impusivity), supported by theory and clinical practice; and in turn, they evidenced the presence of factors within each dimension (Input interference, Loss of focus, Irreflexibility, Impulsivity, Physical and Emotional Hyperactivity), also in line with the reference models. Multiple evidences of its validity are presented in order to become a functional instrument to characterize the expression of ADHD symptomatology, and from this, to focus the appropriate help at individual, family and scholar areas of the child.